Oviposition Deterrent Activity of Some Indigenous Plant Extracts against Pulse Beetle, Callosobruchus chinensis L. Infesting Pea in Storage - Rana, Kiran; Sharma, K. C.; Kanwar, H. S. (International Journal of Bio-resource and Stress Management, 2023)
Oviposition deterrent effect of six aqueous plant extracts from leaves of worm’s wood (Artemisia roxburghii L and A. annua L.), mint (Mentha longifolia L. and M. spicata L.), marigold (Tagetus erecta L.) and seed kernels of dharek (Melia azedarach L.) was studied against the pulse beetle, Callosobruchus chinensis L. at four different concentrations (1%, 2% 4% and 6%) on pea, Pisum sativum under laboratory conditions. The results revealed that all the tested extracts with some variations had oviposition deterrent effect against the pulse beetle as compared to untreated check. It was also observed that reduction in oviposition was increased with the increase in concentration in each treatment. Maximum oviposition deterrent activity was observed in M. azedarach seed kernel extract (62.78%) followed by A. annua (57.23%), T. erecta (51.64%), A. roxburghii (49.41%) , M. spicata (38.90%) and M. longifolia (34.59%) at the highest (6%) concentration and was at par with the deterrent activity observed in A. annua leaves extract but was significantly higher as compared to other extracts indicating thereby that the aqueous extract of both these plant species were equally effective in preventing the oviposition of the pulse beetle on treated pea seeds.